Extensive Surgical Management for Renal Tumors with Inferior Vena Cava Thrombus - Ayati, Mohsen; Nikfallah, Abolghasem; Jabalameli, Parviz; Najjaran Tousi, Vahid; Noroozi, Mohammadreza; Jamshidian, Hasan (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate the outcome in patients with renal cell carcinoma (RCC) and the inferior vena cava (IVC) or the right atrium tumor thrombus that were treated with radical nephrectomy and thrombectomy. Materials and Methods: Eleven of a total of 105 patients who underwent radical nephrectomy due to RCC had tumor thrombus extended to the IVC and/or the right atrium. We evaluated the surgical techniques used and the perioperative mortality and morbidity in these patients. Results: The median age of the patients was 47 years (range, 16 to 59 years). They all underwent radical nephrectomy with cavotomy, tumor thrombus removal, and lymphadenectomy. Eight patients underwent extracorporeal circulation and hypothermic circulatory arrest; 2, temporary venovenous bypass by chevron incision and median sternotomy; and 1, only chevron incision with mobilization of the right lobe of the liver and cross-clamping proximal to the tumor thrombus and cavotomy. In 1 case, a solitary liver metastasis was excised and the patient died within 30 days postoperatively because of massive hemorrhage due to liver metastatectomy. Two patients had invasion to the IVC wall and 7 had pathological lymph node involvement. Four patients were tumor free (follow-up range, 9 to 18 months) and 7 died due to multiple metastases during the follow-up. Conclusion: This study supports the role of extensive surgical treatment as the best initial management of patients with renal cancer extended to the IVC only in highly selected cases.